Novel clinical trial designs emerging from the molecular reclassification of cancer - Mina Nikanjam; Shumei Kato; Teresa Allen; Jason K. Sicklick; Razelle Kurzrock (CA: A Cancer Journal for Clinicians, 2025)
Abstract Next‐generation sequencing has revealed the disruptive reality that advanced/metastatic cancers have complex and individually distinct genomic landscapes, necessitating a rethinking of treatment strategies and clinical trial designs. Indeed, the molecular reclassification of cancer suggests that it is the molecular underpinnings of the disease, rather than the tissue of origin, that mostly drives outcomes. Consequently, oncology clinical trials have evolved from standard phase 1, 2, and 3 tissue‐specific studies; to tissue‐specific, biomarker‐driven trials; to tissue‐agnostic trials untethered from histology (all drug‐centered designs ); and, ultimately, to patient‐centered , N‐of‐1 precision medicine studies in which each patient receives a personalized, biomarker‐matched therapy/combination of drugs. Innovative technologies beyond genomics, including those that address transcriptomics, immunomics, proteomics, functional impact, epigenetic changes, and metabolomics, are enabling further refinement and customization of therapy. Decentralized studies have the potential to improve access to trials and precision medicine approaches for underserved minorities. Evaluation of real‐world data, assessment of patient‐reported outcomes, use of registry protocols, interrogation of exceptional responders, and exploitation of synthetic arms have all contributed to personalized therapeutic approaches. With greater than 1 × 10 12 potential patterns of genomic alterations and greater than 4.5 million possible three‐drug combinations, the deployment of artificial intelligence/machine learning may be necessary for the optimization of individual therapy and, in the near future, also may permit the discovery of new treatments in real time.